After-action Review of Hospital Environments Exploring the ‘New Normal,’ Focusing on Structural Management Aspects and Bacterial Culture in Thai Hospitals Amid the COVID-19 Pandemic - Chongchitpaisan, Wanna; Bandhukul, Adul (Biomedical Sciences and Clinical Medicine, 2024)
OBJECTIVE This study aimed to explore the management of hospital environments during the COVID-19 pandemic, focusing on the structural aspects of ‘new normal’ health services delivery practices and bacterial culture in hospital rooms. METHODS This study employed a cross-sectional design that involved the evaluation of hospital environment management, the detection of indoor bacterial colonies in hospitals, and interviews with healthcare administrators on the ‘new normal’ measures. RESULTS The evaluation form was completed by 543 healthcare division heads from 30 hospitals. Respondents in each group reported that hospitals where they worked had effectively implemented new normal measures, making changes to the structure, processes, and personnel management components in line with the ‘new normal’ concept. The majority of the hospitals investigated, accounting for 71.7%, were found to have pathogenic bacterial counts lower than the permissible limits. The statistical analysis identified a significant association between ventilation, structural management under the ‘new normal’, and bacterial counts (p < 0.05). CONCLUSIONS The incorporation of the structural aspects of new normal practices for managing the workplace environment should be a routine and integral part of efforts to control healthcare-associated infections in hospitals.